Is Schistosomiasis a Risk Factor for Bladder Cancer? Evidence-Based Facts. (1st June 2020) - Jalloh, Mohamed; Cassell, Ayun; Diallo, Thierno; Gaye, Omar; Ndoye, Medina; Mbodji, Mouhamadou M.; Mahamat, Mahamat Ali; Diallo, Abdourahmane; Dial, Cherif; Labou, Issa; Niang, Lamine; Gueye, Serigne M.
Abstract : Background . Globally, approximately 20% of malignancy are caused by infection. Schistosoma infection is a major cause of bladder in most part of Africa. In 2018 alone, there were approximately 549, 393 new cases and 199, 922 deaths from bladder cancer. The presence of Schistosoma ova in the venous plexus of the bladder induces a cascade of inflammation causing significant tissue damage and granulomatous changes. Methodology . A literature review was conducted from 1995 to 2019 using PubMed, Google Scholar, African Journal Online, and Google databases. Relevant data on the association of "Schistosomiasis and Bladder cancer" in sub-Saharan Africa (SSA) were retrieved. Evidence Synthesis . Results from research using animal models to establish the carcinogenesis of Schistosoma and bladder cancer have been helpful but inconclusive. Immunoregulatory cytokines and genetic marker have been identified to play a role in the pathogenesis. In some parts of sub-Saharan Africa, there has been close association of squamous cell carcinoma and histological evidence of Schistosoma ova. Conclusion . There are some data to support the association between schistosomiasis and bladder cancer in sub-Saharan Africa. However, these have been limited by their design and may not sufficiently establish carcinogenesis. There is a need for more genomic and molecular research to better characterize S. haematobium and its effects on the bladder. Such goal will contribute immensely to Schistosoma bladder cancer prevention and control.